LEGALISASI HUKUM ISBAT NIKAH TERHADAP PERKAWINAN YANG TIDAK TERCATAT SEBAGAI WEWENANG PERADILAN AGAMA - Ramlah Ramlah (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Islamic court has function to resolve the receiving, checking, prosecute and make decision on cases submitted in to the field of Islamic Civic Law, and one of which related is to Istbat Nikah, it’s mean that court decisionof marriage to be valid and official. Istbat Nikah happen because the existence of the unlisted marriage before at the official marriage registrar. This act was carried out for their own interests without regard to the law applicable. Istbat Nikah very important to avoid the consequences, such as difficulty of obtaining a birth certificate, obtained a heritatance and earned retirement. To resolve this matter, it is necessary to manage the substantive law applicable in religion justice according to the social and cultural of Indonesian. The reducion of unofficial marriage will be reduce the cases of Istbat Nikah at religious court.Keyword : Legalisasi, Isbat Nikah, dan Pencatatan Perkawinan